Demographics, Presenting Features, and Outcomes of Adult Patients with Ocular Trauma - Leanne M. Clevenger; Jessica L. Cao; Megan S. Steinkerchner; Amy S. Nowacki; Alex Yuan (Journal of Ophthalmology)
Introduction. Ocular trauma is a common cause of permanent vision loss in adults. The combination of an accurate clinical examination and imaging offers the best prognostic indicators for patients and helps to navigate treatment modalities. This is a retrospective chart review of examination and imaging findings for ocular trauma and how they correlate with treatment course and visual acuity (VA) outcomes. Methods. Adult patients with ocular trauma presenting to a single institution between January 2013 and December 2020 were evaluated. Initial examination and imaging findings were compared for associations with each other and with VA outcomes. Results. 136 ocular traumas on 134 patients were included. The median presenting logMAR VA was 2.7 (interquartile range (IQR) 1.2–3.7) with 62% open globe injuries. The most commonly reported finding on initial CT scan was globe deformity (30%), on B-scan was choroidal detachment (20%), and on ultrasound biomicroscopy was intraocular foreign body, ciliochoroidal effusions, or angle recession (21% each). Worse vision was observed for patients positive for retinal detachment on initial B-scan compared to those negative for this finding at 6-month (median logMAR 2.7 vs. 0.5; P<0.0001) and at final post-injury evaluation (median logMAR 3.7 vs. 0.4; P<0.0001). Similarly, worse VA was observed for patients with choroidal detachment on initial B-scan compared to those without this finding at 6-month (median logMAR 1.4 vs. 0.5; P=0.002) and at final post-injury evaluation (median logMAR 2.0 vs. 0.4; P<0.0001). If positive conjunctiva/sclera examination findings were identified, 66% had positive findings on B-scan, whereas if the conjunctiva/sclera examination findings were absent, 41% had positive findings on B-scan (P=0.005). If anterior chamber (AC) examination findings were positive, 59% had positive findings on B-scan, whereas if the AC examination findings were absent, 37% had positive findings on B-scan (P=0.03). Discussion. The predictive value of examination findings in this study may offer insight as to long-term visual prognosis. Positive B-scan or CT findings should increase suspicion for open globe injuries.